Venice from Another Perspective - Cataluccio, Francesco M. (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
This essay with a clearly personal touch is a narrative anchored in cultural texts which deals with experiencing Venice in a multi-faceted way. Talking about his many years of wandering around the city (in the company of, for instance, Joseph Brodsky) and describing places and architectural details important to him, the author argues that especially the mediation of painting, which also documented the history of Venice, allows for a better understanding of the phenomenon of the city. This fusion of the two modalities of experience is also reflected in the structure of the text, which closes the reflection on the contemporary condition of the city and various threats which Venice has to face.